Preserving Muscle Mass During GLP-1RA Induced Weight Loss Using Combined HIFEM and Synchronized Radiofrequency Technology - McCoy, JD; Schoeff, Jonathan; Goldfarb, Richard (Archives of Clinical and Biomedical Research, 2025)
Background: Glucagon-like peptide-1 receptor agonists (GLP-1RAs) are now widely prescribed for weight loss. However, rapid weight reduction often leads to unintended muscle mass loss, which may reduce basal metabolic rate, making long-term weight maintenance more challenging. Study Aim: This chart review examines the effects of combined HIFEM and RF technology on preserving skeletal muscle mass during GLP-1RA weight loss treatment. Methods: 63 participants were divided into 3 cohorts: group G (n=21, 2 males, 19 females, 48.3±21.0 years, BMI 26.8±3.3 kg/m2) received only GLP-1RA weight loss treatment, group GHR (n=21, 6 males, 15 females, 46.0±13.1 years, BMI 25.9±3.3 kg/m2) received GLP-1RA treatment with HIFEM+RF treatment, and group HR (n=21, 7 males, 14 females, 50.8±11.3 years, BMI 24.6±3.4 kg/m2) received only HIFEM+RF treatment. Body composition was assessed using bioelectrical impedance analysis. Results: Group G experienced a decrease in muscle mass, averaging -2.9±1.3 lbs. Conversely, group GHR gained +1.0±3.1 lbs of muscle, and group HR gained +1.8±3.1 lbs of muscle. Changes in muscle mass differed significantly between groups G and HR, as well as G and GHR (p<0.001). Conclusion: The results indicate combining HIFEM+RF with GLP-1RA weight loss therapy effectively mitigates muscle mass loss. Participants receiving the combined intervention not only maintained but increased muscle mass by 1.0 lb, resulting in a net difference of 3.9 lbs compared to GLP-1RA treatment alone.